THE INFLUENCE OF ECO-BRAND, ECO-LABEL, AND ENVIRONMENTAL ADVERTISING ON CONSUMER PURCHASE INTENTION OF AQUA RECYCLE PLASTIC BOTTLE BRAND (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
In the current era of globalization, the earth is facing a serious problem known as global warming. The continued use of environmentally unfriendly plastic products can lead to various serious environmental problems. Currently, plastic waste from bottled drinking water (AMDK) contributes to the increase in waste piles because the bottles are made of plastic and require a large space in landfills. This study aims to determine the influence of eco-brand, eco-label, and environmental advertising on consumer purchase intentions for the Aqua Recycle Plastic Bottle product. This research uses a quantitative descriptive method with data collection techniques through a survey of 100 respondents who are consumers of the Aqua Recycle Plastic Bottle. The independent variables in this study are eco-brand, eco-label, and environmental advertising, while the dependent variable is consumer purchase intention. The data were analyzed using analytical methods used include, validity test, classical assumption test, reliability test multiple linear regression, t-test, and f-test. The results of this study indicate that eco-brand have not a significant influence on consumer purchase intentions. Eco-label, and environmental advertising have a significant influence on consumer purchase intentions.
Keywords: Eco-Brand; Eco-Label; Environmental Advertising; Purchase Intention